From Plan–Do–See to Real Differentiation: Tracing Teachers’ Shifts in Differentiated Instruction Across Lesson Study (A Case Study in Vocational High Schools) - Rahmawati Upa; Paldy; Opik Dwi Indah; Suci Damayanti; Nurthasya (Universitas Islam Negeri Palopo, 2024)
This study traces teachers’ shifts in differentiated instruction across three Lesson Study (Plan–Do–See) cycles in a vocational high school context through an open-class program on fantasy text learning. Using a qualitative case study approach, the research examines differentiated instruction as it emerged through iterative redesign of (a) grouping arrangements, (b) tiered group tasks aligned with students’ readiness, and (c) teacher responsiveness to passive individuals during group work. Data were collected across planning, implementation, and reflection stages, including lesson plans and revised materials, classroom observation notes focused on participation patterns, and records of post-lesson reflection discussions. Findings indicate a clear developmental trajectory across cycles. In Cycle I, heterogeneous grouping was associated with unequal participation, as higher-ability students dominated discussion and presentation while lower-ability students remained largely silent. In Cycle II, redesign toward homogeneous grouping combined with tiered group tasks was linked to increased participation among previously passive students, particularly within lower-ability groups. In Cycle III, differentiation was strengthened further through deliberate teacher attention to passive individuals across all ability groups, indicating a shift from group-level differentiation to more responsive, individual-level support. The study highlights how Lesson Study can function as an evidence-based redesign mechanism for developing “real differentiation” in vocational classrooms by progressively refining learning conditions, task calibration, and in-the-moment teacher responsiveness. Practical implications emphasize evaluating grouping assumptions, integrating grouping with tiered tasks, monitoring passivity at the individual level, and using the “See” stage to anchor redesign in concrete participation evidence.